The impact of creative activities involving cooking oil waste on sustainable environments / Hairulnisak Merman ... [et al.] - Merman, Hairulnisak; Tagie, Gladys; W. Mohd Apandi, Wan Nurhasyimah; Ismail, Issarezal; Mohd Jainal, Aslina (Universiti Teknologi MARA, Perak, 2023)
Disposal of cooking oil waste into public places has adverse effects on the environment such as clogged drains, polluted rivers, and soil damaged by the loss of mineral resources. Clogged drains cause pest breeding, while contaminated water sources have an impact on the destruction of aquatic life. Despite various efforts, the issue of pollution continues to occur in line with uncontrolled development as well as increasing population growth. The objective of this study is to identify the impact of the implementation of creative activities on environmental preservation. The study uses qualitative methodology as its main research approach. Researchers collect information through key data collection methods such as interviews, observations, and fieldwork. Secondary methods are derived from data sources such as books, journals, and magazines. The results of this study found that the creative activities implemented became one of the solutions in the effort to reduce the disposal of cooking oil waste by taking a recycling and reuse approach. In fact, this activity can also make room for the locals to learn how to recycle cooking oil waste into a useful ingredient. Therefore, this study should be continued by intensifying creative activities to increase public knowledge and awareness of the potential of cooking oil waste to reduce environmental pollution, especially water pollution. This action matches the government's call for the success of the Sustainable Development Goals (SDGs), which focuses on the 12th goal of Responsible Consumption and Production.